Respuesta :

Answer:

-13

Step-by-step explanation:

-68 = 5y-3 First you move the -3 by adding 3 to both sides to get -65 =5y

Then you divide 5 by both sides to get y=-13

Space

Answer:

y = -13

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Step-by-step explanation:

Step 1: Define equation

-68 = 5y - 3

Step 2: Solve for y

  1. Add 3 to both sides:                    -65 = 5y
  2. Divide both sides by 5:                -13 = y
  3. Rewrite:                                         y = -13

Step 3: Check

Plug in y to verify it's a solution.

  1. Substitute:                    -68 = 5(-13) - 3
  2. Multiply:                        -68 = -65 - 3
  3. Subtract:                       -68 = -68

And we have our final answer!